2022
DOI: 10.1007/s10064-022-02687-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water content on the basic friction angle of porous limestones—experimental study using an automated tilting table

Abstract: An accurate evaluation of the shear strength of discontinuities is frequently a key aspect for determining the safety of mining and civil engineering works and for solving instability issues at rock mass scale. This is usually done by using empirical shear strength criteria in which the basic friction angle (φb) is a relevant input parameter. Tilt testing is probably the most widespread method to obtain the φb due to its simplicity and low cost, but previous research has demonstrated that the results are stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…As Rabat et al [41] found, the water distribution on rock surfaces is unavoidably slightly different for each test during the test process. Therefore, in this paper, to control the moisture condition of rock surface, the saturated samples were placed in the air to lose water naturally, and φ b was tested during the water loss process.…”
Section: The Influence Of Moisture Condition On φBmentioning
confidence: 92%
See 3 more Smart Citations
“…As Rabat et al [41] found, the water distribution on rock surfaces is unavoidably slightly different for each test during the test process. Therefore, in this paper, to control the moisture condition of rock surface, the saturated samples were placed in the air to lose water naturally, and φ b was tested during the water loss process.…”
Section: The Influence Of Moisture Condition On φBmentioning
confidence: 92%
“…The basic friction angle (φb) is an essential parameter in the shear strength model of rock joints, which is an inherent material property related to the rock type, mineral composition and particle size [7,18,41,49]. It has been summarized that the φb is approximately 25°~30° for sedimentary rocks, and 30°~35° for igneous and metamorphic rocks [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations